Implementation of Full Convertibility of the Nepalese Rupee in the Capital Account - Institute for Policy Research; Development (NRB Economic Review, 2000)
Abstract from the Report submitted to Nepal Rastra Bank by Institute for Policy Research Development (IPRAD).